An institutional evaluation of radiotherapy with concurrent and adjuvant temozolomide exclusively in grade III gliomas - Darisi, Naga Chandra Sekhar; Konakalla, V. L. Anusha; Koyyala, Venkata Pradeep Babu (International Journal of Research in Medical Sciences, 2021)
Background: Gliomas are the most common tumors that develop from glial cells in the brain. As per WHO classification, grade III (high-grade) gliomas are usually treated by surgery followed by radiotherapy. Concurrent and adjuvant chemotherapy with temozolomide (TMZ) is showing new hope in the management. Methods: Prospective study was conducted in 20 WHO grade III glioma patients at GSL medical college and general hospital for a period of 2 years (August 2019 to July 2021) to evaluate the role of concurrent and adjuvant TMZ with radiation in the treatment of grade III gliomas. The primary objectives of the study were to determine toxicity and response rates in our set of patients. The secondary objectives were to determine progression-free survival and overall survival. Results: Majority were males (80%) in the age group of 30 to 49 (75%). 40% of gliomas were in the temporal lobe. Headache was the most presenting symptom (60%) followed by seizures (35%).70 to 80 Karnofsky performance status/ KPS score was seen in 70% of cases. None of the patients in the study had grade 3 or 4 toxicities. 40% had a complete response according to MacDonald’s criteria. At a median follow-up of 10 months, 25% of patients had disease progression and 1yr overall survival was 95%. Conclusions: TMZ combined with radiation was well tolerated in our set of patients with grade III gliomas without any significant toxicity.